PENGARUH AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN TARI DAERAH SETEMPAT KELAS X SMA NEGERI 8 PADANG - Merisa Amriyeni; Idawati Syarif; Zora Iriani (SENDRATASIK UNP, 2013)
Abstract   This study includes all of the experiments penelitiaan draft only randomized control group design with sampling techniques used are Culster sampling. To get results on the cognitive learning to use the test results to learn, for the affective and psychomotor used observation sheet. The study's findings that student learning outcomes in the cognitive domain to obtain the experimental class average - average  80.82 while the control class has an average - average 70.79.   Kata Kunci: Ranah Kognitif